2009
DOI: 10.1093/toxsci/kfp219
|View full text |Cite
|
Sign up to set email alerts
|

Probucol Increases Glutathione Peroxidase-1 Activity and Displays Long-Lasting Protection against Methylmercury Toxicity in Cerebellar Granule Cells

Abstract: Methylmercury (MeHg) is an environmental neurotoxicant whose molecular mechanisms underlying toxicity remain elusive. Here, we investigated molecular events involved in MeHg-induced neurotoxicity in cultured cerebellar granule cells (CGCs) as well as potential protective strategies for such toxicity. Glutathione peroxidase, isozyme 1 (GPx-1) activity was significantly (p = 0.0017) decreased at 24 h before MeHg-induced neuronal death (day in vitro 4). This event was related to enhanced susceptibilities to hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 130 publications
(104 citation statements)
references
References 45 publications
5
96
0
3
Order By: Relevance
“…There have also been many reports of MeHg causing decreased GPx activity in vitro Hirota et al, 1980;Kromidas et al, 1990). Farina et al (2009) reported that the overexpression of GPx1, which is the most abundant version of GPx, prevented MeHg-induced neuronal death, indicating that GPx1 is an important molecular target that is involved in MeHg-induced neurotoxicity. They didn't determine how GPx1 was inhibited, but suggested that selenol groups (which have lower pKa values than do thiol groups) in the enzyme were involved.…”
Section: Oxidative Stress and S-mercurationmentioning
confidence: 99%
“…There have also been many reports of MeHg causing decreased GPx activity in vitro Hirota et al, 1980;Kromidas et al, 1990). Farina et al (2009) reported that the overexpression of GPx1, which is the most abundant version of GPx, prevented MeHg-induced neuronal death, indicating that GPx1 is an important molecular target that is involved in MeHg-induced neurotoxicity. They didn't determine how GPx1 was inhibited, but suggested that selenol groups (which have lower pKa values than do thiol groups) in the enzyme were involved.…”
Section: Oxidative Stress and S-mercurationmentioning
confidence: 99%
“…Specific attention should be paid to its organometallic compound, methylmercury, because: i) it has recognized properties as a human neurodevelopmental toxicant (Grandjean and Landrigan, 2006); ii) poisoning incidents with methylmercury have demonstrated the potential of this pollutant as neurotoxicant and its serious health consequences (Castoldi et al, 2008;Ekino et al, 2007;Grandjean et al, 2010;Nakagawa et al, 2002); iii) millions of people are nowadays chronically exposed to this contaminant and there is epidemiological (Marsh et al, 1987; Pinheiro et al, 2007;Yokoo et al, 2003) and experimental (Castoldi et al, 2008;Farina et al, 2009;Vendrell et al, 2007Vendrell et al, , 2010 evidence of the toxic effects of chronic exposure to this metal especially for the nervous system; and iv) previous results from the INMA birth cohort of Valencia (Spain) showed elevated levels of this pollutant in umbilical cord blood, where 70% of newborns had mercury levels above US EPA recommended level, i.e. 5.8 μg/L of MeHg (Ramon et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, probucol increased GPx activity. Likewise, overexpression of GPx-1 in cultured cerebellar granule cells resulted in neuroprotection against methylmercury-induced cell death (Farina et al, 2009). Figure 2 summarizes some of these findings.…”
Section: Cell-based Methods For Predicting Neurotoxicity Of Environmementioning
confidence: 88%
“…Figure 2 summarizes some of these findings. On the other hand, no effects were found in reduced and oxidized glutathione levels, glutathione reductase and catalase activity, nor on neuronal glutamate uptake or intracellular calcium, after using the same protocol for methylmercury exposure (Farina et al, 2009). Altogether, these results suggest that oxidative stress driven by inhibition of glutathione peroxidase may be one of the first hallmarks of methylmercury-induced neurotoxicity in the development of cerebellar granule cells, a finding also observed in mice exposed to methylmercury (Franco et al, 2009).…”
Section: Cell-based Methods For Predicting Neurotoxicity Of Environmementioning
confidence: 88%